2023
DOI: 10.3389/fimmu.2023.1166212
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of the brainstem dorsal motor nucleus ameliorates acute pancreatitis

Abstract: IntroductionInflammation is an inherently self-amplifying process, resulting in progressive tissue damage when unresolved. A brake on this positive feedback system is provided by the nervous system which has evolved to detect inflammatory signals and respond by activating anti-inflammatory processes, including the cholinergic anti-inflammatory pathway mediated by the vagus nerve. Acute pancreatitis, a common and serious condition without effective therapy, develops when acinar cell injury activates intrapancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…For example, a previous study has shown that pancreatitis worsens following vagotomy or use of a nAChR antagonist, while in contrast the α7nAChR agonist GTS-21 protects via inhibition of macrophage pro-inflammatory cytokine production (Westerloo et al 2006 ). Additionally, the results of a recent study demonstrated that direct optogenetic stimulation of the efferent vagus nerve at the level of the dorsal motor nucleus (DMN) in the brainstem significantly reduces the severity of acute pancreatitis via a nAChR-dependent mechanism (Thompson et al 2023 ). These observations demonstrate the potential therapeutic relevance of activating neuronal cholinergic pathways to reduce the severity of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study has shown that pancreatitis worsens following vagotomy or use of a nAChR antagonist, while in contrast the α7nAChR agonist GTS-21 protects via inhibition of macrophage pro-inflammatory cytokine production (Westerloo et al 2006 ). Additionally, the results of a recent study demonstrated that direct optogenetic stimulation of the efferent vagus nerve at the level of the dorsal motor nucleus (DMN) in the brainstem significantly reduces the severity of acute pancreatitis via a nAChR-dependent mechanism (Thompson et al 2023 ). These observations demonstrate the potential therapeutic relevance of activating neuronal cholinergic pathways to reduce the severity of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Such approaches will allow further interrogation of this circuitry and should be applied with pVNS to clarify afferent and efferent vagal signaling after orthopedic surgery. 7,28,60 Using our pVNS protocol, we found that weekly pVNS resolved postoperative allodynia on day 22 after surgery. Notably, it took 3 weeks and 4 pVNS treatments to effectively reduce bilateral mechanical paw allodynia to baseline levels.…”
Section: Discussionmentioning
confidence: 92%
“…Despite historical controversy about the capacity of CVN DMV to impact HR, our results demonstrate that optogenetic and chemogenetic activation of Chat+ DMV neurons each caused robust bradycardia (∼56% and ∼65.5% of resting HR, respectively) in awake, behaving mice. Cardioinhibitory responses using optogenetic techniques in urethane-anesthetized rats and ketamine/xylazine-anesthetized mice demonstrated variable strength of the response, 18 , 21 implicating differences in anesthesia for differences in effect size. Alternatively, previous species used (namely cats and rats) may exhibit a lesser degree of DMV driven bradycardia than mice because of differences in vagal tonus.…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that direct electrical stimulation of DMV does not change chronotropy, 7 , 16 while others demonstrate local activation (chemical, electrical, optogenetic, or chemogenetic) elicits bradycardias even if only modestly. 17 , 18 , 19 , 20 , 21 However, no activation technique in awake animals used to date rules out incidental stimulation of either neighboring nucleus tractus solitarius (NTS) neurons or inhibitory interneurons within DMV. Stimulation of this latter population could significantly dampen the impact of cholinergic premotor neuron stimulation.…”
Section: Introductionmentioning
confidence: 99%